The development of Business Ethics in front of the progress of organizational neuroscience and neuroethics - González Esteban, Elsa (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
Organizational neuroscience and neuroethics are proving to have already made a number of advances in the discovery of both cognition and human behaviour. Those progresses invite us to rethink some of the classical assumptions on which have been developed applied ethics. This article focuses on the analysis about how the progresses of the neurosciences affect our understanding of business ethics and its future development, specially in its organizational level. In order to achieve this objective, the paper is structured in two steps. On the one hand, it considers whether such developments undermine or erode normative foundations of business ethics. On the other hand, it tries to discover the implications of such developments have for business ethics in its practical development.